1991
DOI: 10.1002/actp.1991.010421214
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of moulded shapes from Egyptian corncobs‐bisphenol polycondensate resins and aluminium powder

Abstract: Different types of moulded shapes were prepared from Egyptian corncobs‐bisphenol polycondensate resins and aluminium powder. Modifications of the produced resin with phenol‐formaldehyde, naphthalene‐formaldehyde, and anthracene‐formaldehyde, were performed. The electrical conductivity of the samples increases with the increase of temperature and aluminium concent. All samples reveal semiconducting behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In the past few years, a rapidly growing demand for bisphenol A in industrial scale is for use in high-tech production, such as compact discs and digital video discs [1][2][3][4]. Bisphenol A corncobs (BPACC) is synthesized through the condensation reaction of BPA and the powder of Egyptian corncobs [5,6]. Both chemical analysis and IR spectroscopy have shown that BPACC resin has a complicated structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, a rapidly growing demand for bisphenol A in industrial scale is for use in high-tech production, such as compact discs and digital video discs [1][2][3][4]. Bisphenol A corncobs (BPACC) is synthesized through the condensation reaction of BPA and the powder of Egyptian corncobs [5,6]. Both chemical analysis and IR spectroscopy have shown that BPACC resin has a complicated structure.…”
Section: Introductionmentioning
confidence: 99%